PENGARUH BUDAYA ETIS ORGANISASI DAN PEMAHAMAN GOOD GOVERNANCEPADA KINERJA AUDITOR KANTOR AKUNTAN PUBLIK DI BALI - purnama dewi putu (Jurnal Ilmiah Akuntansi & Bisnis, 2016)
This research examines the influence of ethical culture organization and understanding of good governance towards job performance of an auditor of the public accounting firm. Number of respondents taken in this research were 60 respondents. Data was obtained through questionnaire by distributing it to the auditors of the public accounting firm. Multiple linear regression analysis was used within this research.This research indicates that ethical culture organization has positive impacts on their job performance. understanding of good governance has positive impacts on the job performance of an auditor.